Research on the Radiation Effects and Compact Model of SiGe HBT - Sun, Yabin (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2018)
This book primarily focuses on the radiation effects and compact model of silicon-germanium (SiGe) heterojunction bipolar transistors (HBTs). It introduces the small-signal equivalent circuit of SiGe HBTs including the distributed effects, and proposes a novel direct analytical extraction technique based on non-linear rational function fitting. It also presents the total dose effects irradiated by gamma rays and heavy ions, as well as the single-event transient induced by pulse laser microbeams. It offers readers essential information on the irradiation effects technique and the SiGe HBTs model using that technique.